Minefill 2020-2021 Proceedings of the 13th International Symposium on Mining with Backfill, 25-28 May 2021, Katowice, Poland - Hassani, Ferri; Palarski, Jan; Sokoła-Szewioła, Violetta; Strozik, Grzegorz (Taylor & Francis, 2021)
The series of International Symposiums on Mining with Backfill explores both the theoretical and practical aspects of the application of mine fill, with many case studies from both underground and open-pit mines. Minefill attendees and the Proceedings book audience include mining practitioners, engineering students, operating and regulatory professionals, consultants, academics, researchers, and interested individuals and groups. The papers presented at Minefill symposiums regularly offer the novelties and most modern technical solutions in technology, equipment, and research. In that way, the papers submitted for the Minefill Symposia represent the highest quality and level in the conference domain. For the 2020-2021 edition organizers hope that the papers presented in this publication will also be received with interest by readers around the world, providing inspiration and valuable examples for industry and R&D research.